2018
DOI: 10.3389/fnagi.2018.00067
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Network Disruptions and Regional Amyloid Beta in Cognitively Normal Adults

Abstract: The accumulation of amyloid plaques is one of the earliest pathological changes in Alzheimer’s disease (AD) and may occur 20 years before the onset of symptoms. Examining associations between amyloid pathology and other early brain changes is critical for understanding the pathophysiological underpinnings of AD. Alterations in gray matter networks might already start at early preclinical stages of AD. In this study, we examined the regional relationship between amyloid aggregation measured with positron emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 61 publications
1
21
1
Order By: Relevance
“…A between-group analysis performed by Chetelat et al indicated that, in participants with SCD, individuals with a higher level of amyloid deposition showed significant gray matter atrophy compared with individuals with a low level of amyloid deposition [ 180 ]. Further correlation analyses between imaging modalities also supported the relationship between amyloid pathology and reduced integrity of brain structures in both the gray matter and WM ranging from voxel level to brain connectome properties in subjects with SCD [ 101 , 181 , 182 ]. Ferreira et al tested a disease severity index generated from a multivariate analysis involving amyloid PET and structural MRI data, and this index may potentially identify individuals with SCD with the AD-like pattern, as an appropriate risk population [ 183 ].…”
Section: Multimodal Neuroimaging Studiesmentioning
confidence: 83%
See 2 more Smart Citations
“…A between-group analysis performed by Chetelat et al indicated that, in participants with SCD, individuals with a higher level of amyloid deposition showed significant gray matter atrophy compared with individuals with a low level of amyloid deposition [ 180 ]. Further correlation analyses between imaging modalities also supported the relationship between amyloid pathology and reduced integrity of brain structures in both the gray matter and WM ranging from voxel level to brain connectome properties in subjects with SCD [ 101 , 181 , 182 ]. Ferreira et al tested a disease severity index generated from a multivariate analysis involving amyloid PET and structural MRI data, and this index may potentially identify individuals with SCD with the AD-like pattern, as an appropriate risk population [ 183 ].…”
Section: Multimodal Neuroimaging Studiesmentioning
confidence: 83%
“…Both groups of researchers showed that the gray matter network of individuals with SCD was more randomly organized than HCs, and the disrupted network properties were associated with a steeper decline in global cognition and a higher risk of disease progression. Moreover, Ten Kate et al [ 101 ] observed an association between a higher level of global amyloid deposition and lower clustering and fewer small-world properties of gray matter structural networks in subjects with SCD. Overall, although some negative results have been reported, individuals with SCD related to AD have been repeatedly shown to present a reduced gray matter volume and cortical thickness and a disrupted gray matter network.…”
Section: Structural Mri and Diffusion Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…We examined relationships between grey matter network small-world coefficient and established Alzheimer’s disease markers within mutation carriers. Previous research suggested grey matter networks may be disrupted in response to Aβ accumulation, precipitating cognitive decline ( Ten Kate et al , 2018 ). For this reason, our models included either precuneus PET Aβ as a predictor and grey matter network metrics as outcomes or grey matter network metrics as a predictor and cortical thickness (precuneus), brain metabolism (meta-ROI), or cognition (DIAN cognitive composite) as the respective outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…In pre-dementia stages, such loss of network integrity predicts clinical progression and cognitive decline ( Dicks et al , 2018 ; Tijms et al , 2018 ). The presence of amyloid β (Aβ) pathology in cognitively normal individuals has also been associated with grey matter network alterations ( Tijms et al , 2016 ; Ten Kate et al , 2018 ; Voevodskaya et al , 2018 ). Together, these observations suggest that these network properties change over the course of Alzheimer’s disease, from early stages, and that individual grey matter network extractions could possibly be used to monitor disease progression.…”
Section: Introductionmentioning
confidence: 99%